The motif of the status of professional activity and its place in the development of labor potential at universities in the public-administrative perspective - Moroz, Svitlana A.; Chala, Yuliia (НТУ "ХПІ", 2016)
This article presents an analysis of the responses of experts who have assessed the significance of the motif of professional teacher status at higher educational establishments and comparisons of influence power of its main formation actors on employment opportunities at universities. In addition, the article presents conclusions on the possible impact of government on the effectiveness of labor potential of universities within the process of development and enhancement of the status of university teacher’s professional motive.
Мотив статусу професійної діяльності та його місце в розвитку трудового потенціалу у вищих навчальних закладах у суспільно-адміністративній перспективі
Keywords: motivation of professional activity; employment potential at universities; university teacher profession; employment opportunities at universities; професійна діяльність; науково-педагогічні працівники; трудовий потенціал ВНЗ; професія викладача ВНЗ